A Review on Image Segmentation Technique (International Journal of Innovative Research in Computer Science & Technology, 2020)
Making a segment of an image or any object  is what segmentation is all about. The first stages in image  segmentation are pattern recognition and picture analysis.  We may conduct significant research topics in the  segmentation of video with dynamic backdrop in the  computer vision area and image analysis. In image  processing and analysis, picture segmentation is the most  common judging or analyzing function. Picture  segmentation is the division of an image into distinct areas  that are same or similar in some aspects and homogeneous  in others. The outcomes of picture segmentation have an  impact on image greater tasks and evaluation  Characterization and depiction of objects, as well as  feature measurement, are all part of image analysis. The  categorization of objects is followed by a higher-order job.  As a result, image segmentation relies heavily on  characterization, visualization of the part of attention in  any image, and demarcation. The current methods of  picture segmentation are examined using various  algorithms in order to allow user interaction with images.  The review of picture segmentation is presented in this  article utilizing several methods.
Keywords: Image Segmentation; Image AnalysiS; Segment; Video